2021
DOI: 10.1186/s13561-021-00337-9
|View full text |Cite
|
Sign up to set email alerts
|

Health system efficiency in OECD countries: dynamic network DEA approach

Abstract: Background In recent years, measuring and evaluating the efficiency of health systems has been explored in the context of seeking resources to ensure the sustainability of ‘countries’ health and social systems and addressing various crises in the health sector. The study aims to quantify and compare the efficiency of OECD health systems in 2000, 2008, and 2016. The contribution to research in the field of efficiency in the healthcare system can be seen in the application of Dynamic Network Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 57 publications
(115 reference statements)
2
28
0
Order By: Relevance
“…Based on the DEA results, and especially on mean results (Table 4 ) the health systems of European countries could be grouped into three categories of efficiency [ 11 , 18 , 27 ]: category 1 : high efficiency (0.75–1): Austria, Croatia, Cyprus, Czechia, Denmark, Estonia, Finland, Iceland, Ireland, Latvia, Luxembourg, Malta, Norway (only country with very high efficiency (= 1), Portugal, Slovakia, Slovenia, Switzerland; category 2 : average efficiency: (0.5–0.75): Belgium, Bulgaria, France, Germany, Greece, Hungary, Netherlands, Poland, Spain, Sweden, UK’ category 3: low efficiency (< 0.5): Italy and Romania. States with low efficiency health systems have demonstrated vulnerabilities in how resources were used in the first year of the pandemic, by reference to the needs.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the DEA results, and especially on mean results (Table 4 ) the health systems of European countries could be grouped into three categories of efficiency [ 11 , 18 , 27 ]: category 1 : high efficiency (0.75–1): Austria, Croatia, Cyprus, Czechia, Denmark, Estonia, Finland, Iceland, Ireland, Latvia, Luxembourg, Malta, Norway (only country with very high efficiency (= 1), Portugal, Slovakia, Slovenia, Switzerland; category 2 : average efficiency: (0.5–0.75): Belgium, Bulgaria, France, Germany, Greece, Hungary, Netherlands, Poland, Spain, Sweden, UK’ category 3: low efficiency (< 0.5): Italy and Romania. States with low efficiency health systems have demonstrated vulnerabilities in how resources were used in the first year of the pandemic, by reference to the needs.…”
Section: Resultsmentioning
confidence: 99%
“…These factors are also a part of the SDG 3. Prevention programs and systems of health literacy, which have to be a part of educational systems, play an important role in the process of reducing differences in health among countries ( 51 , 68 70 ). In recent years, environmental literacy has been an important topic for many countries in relation to environmental strategies and reduction of environmental risks.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the similarities of effectiveness and feasibility of measures in the short run and the long run, we found that more effective and applicable measures in the short run and the long run were those the ones that increased the efficiency of health resources and the correct use of resources, leading to making a resilient health system against sanctions. Several studies have concluded that the main issue in all health systems is inefficiency and the waste of health resources [ 35 , 36 ]. Thus, it is essential to ensure efficiency improvement to make a resilient health system cope with catastrophic events.…”
Section: Discussionmentioning
confidence: 99%